Keunggulan Bersaing, Aliansi Strategis, dan Manajemen Pengetahuan: Sebuah Kerangka Konseptual - Khairul Ikhwan; Clarisa Alfa Lionora; Ivo Novitaningtyas; Budi Rahardjo (Universitas Medan Area, 2022)
Competitive advantage is one of the success factors of businesses in managing their resources and capabilities. An organization must be able to outperform the competition through the creation of unique, rare, and valuable products. Business units can increase their competitiveness through strategic alliances. Theoretical studies related to the factors that a business unit can carry out in the formation of alliances are necessary for increased competitive advantage. The purpose of this study: first, to provide a review of the latest literature related to competitive advantages that can be achieved through alliances. Second, identify the upcoming research agenda. Third, it recommends a new research framework. This research used the systematic literature review method. The data used in this article comes from proposed future research agendas from 23 previous research articles published in the last 5 years (2018-2022). The output of this study is the recommendation of a theoretical framework.